(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Previous studies have referred that the breast cancer, with particular histological traits, can be affected by the reproductive factors. In the current study, we employed 30 breast cancer cases for women in age (15-55 years) to study how factors such as microscopic screening, gross examination, as well as the age, can impact on histological type and grade of tumor. After the organ eradication from the patients, the tissue samples were picked, as fast as possible, and placed in 10% formalin directly. In such a way, we maintained the cells and cellular components in a situation that can be described as similar as possible to the living cells and preserved the antigenicity in order to be processed without any modification. Samples were divided depending on various factors, such as anatomical location, the nodal status, and tumor relationship to surgical margin, weight, size, and age. Each sample was sectioned and fixed onto a private embedding cassette to keep the tissue treatment. The histochemical stains, which is include the eosin and hematoxylin, had utilized to afford a disparity to tissue sections. We found that the majority of the 30 women with breast cancer were at age (31-40 years) and that 12 patients of them were involved left breast, while the other 18 patients included right breast. In agreement with previous studies that have investigated the level of risk of histological subgroups, our study concludes that the link between breast cancer risks and reproductive factors is vary depending on the histological structure of the tumor.